Status and problems of qualitative research in education: Divulgation, research and access of university teaching staff - Fernández-Navas, Manuel; Alcaraz-Salarirche, Noelia; Pérez-Granados, Laura (Education Policy Analysis Archives, 2021)
This paper presents a reflexive panorama focusing the problems of divulgation of qualitative research results in Spain. In our experience, we observe that there is no equity between quantitative and qualitative methodologies, with a clear predominance of quantitative methods, which has made reliability in the qualitative methodology as a rigorous research approach to be seen strongly affected. To inquire into this situation, the production in high-impact Spanish journals of the last five years has been analysed, classifying the type of articles published according to methodology, as well as their focus and scope policies. On the other hand, in order to contrast the information with the documentary analysis, researchers in qualitative research, as well as students, have been interviewed about the problem of publishing in journals with high impact and the difficulties in obtaining research projects with this approach. Among the reasons that have led to this situation we find that, the access of university professors, focused mainly on merits of publications and research; and the preference of quantitative work impact journals derived, among other issues related to hegemonic thinking about how rigorous knowledge is generated, produces significant imbalances between both methodologies. We conclude the article considering possible proposals that presumably will value the richness of qualitative research as an indispensable part of scientific thinking in education.